Tocotrienols and Oxidative stress in oocytes and developing embryos / Yuhaniza Shafinie Kamsani and Mohd Hamim Rajikin. - Kamsani, Yuhaniza Shafinie; Rajikin, Mohd Hamim (Universiti Teknologi MARA Cawangan Selangor, 2017)
This review summarizes the impact of tocotrienols (TCTs) as antioxidants in minimizing oxidative stress (OS), particularly in embryos exposed to OS causing agents. OS level is increased, for example, by nicotine, a major alkaloid content in cigarette, which is also a source of exogenous reactive oxygen species (ROS). Increased nicotine-induced OS increases cell stress response, which is a common trigger leading to embryonic cell death. Having more profound anti-oxidative stress effects than its counterpart tocopherol, TCTs improve blastocyst implantation, foetal growth, pregnancy outcome and survival of the neonates affected by nicotine. In reversing cell developmental arrest caused by nicotine-induced OS, TCTs enhances PDK-1 expression in the P13K/Akt pathway and permit embryonic development beyond the 4- cell stage with the production of more morulae. At the cytoskeletal level, TCTs increase the number of nicotine-induced apoptotic cells, through caspase 8 activation in the mitochondria. TCTs facilitate rough endoplasmic reticulum (rER) stress-mediated apoptosis and autophagy, resulting from nicotine-induced OS. Reduced vesicular population in TCT supplemented oocytes on the other hand may suggest reduced secretion of apoptotic cell bodies thus probably minimizing vesicular apoptosis during oocyte maturation. Further extensive research is required to develop TCTs as a tool in specific therapeutic approaches to overcome the detrimental effects of OS.